How Feasible Is the Scaling-Out of Livelihood and Food System Adaptation in Asia-Pacific Islands? - Butler, James R. A.; Rochester, Wayne; Skewes, Tim D.; Wise, Russell M.; Bohensky, Erin L.; Katzfey, Jack; Kirono, Dewi G. C.; Peterson, Nate; Suadnya, Wayan; Yanuartati, Y.; Handayani, Tarningsih; Habibi, Putrawan; et al. (Frontiers in Sustainable Food Systems, 2020)
The sustainable development and food security of islands in the Asia-Pacific region is severely compromised by climate change, sea level rise and compounding socio-economic issues. To achieve a step-change in food production and climate adaptation, livelihoods must rapidly transform. Food security programs continue to apply the ‘pipeline’ model of scaling-out technological innovations, but do not account for the social-ecological complexity of islands. We tested the feasibility of scaling-out adaptation strategies in two provinces in the region: Nusa Tenggara Barat in Indonesia, and West New Britain in Papua New Guinea. Guided by a sub-district typology of resource use, we trialled a participatory, systems-based livelihood adaptation pathways approach in sub-district case studies. The process aimed to mainstream social learning and future uncertainty into community development decision-making, yielding ‘no regrets’ adaptation strategies to transform livelihoods. We tested two assumptions: first, that because the contexts of all villages were homogenous, strategies were sufficiently similar to enable scaling-out across the provinces; second, that the sub-district typologies would assist scaling-out within each type. The results showed that the first assumption was untenable: there was very little similarity amongst villages’ strategies; only sustainable fisheries management was scalable amongst coastal villages. The second was marginally tenable, because there were strong similarities amongst villages in an off-shore island type. When pooled into classes of adaptation strategy, most related to practice and behaviour change, and addressed systemic social issues; very few were technological. Our results suggest that scaling-out livelihood and food system innovations is not feasible due to the complex social-ecological contexts within islands, caused by steep climate gradients, natural resource and cultural diversity. We discuss the limitations of a resource use typology that aimed to mitigate this complexity and guide scaling-out. Instead we argue that appropriate social learning approaches akin to livelihood adaptation pathways must be mainstreamed into existing community development decision cycles, thereby ‘scaling-up’ and ‘scaling-deep’ to tackle institutional, political and cultural barriers to transformation. We discuss the implications of our recommendations for government and donor support for food security programs in islands of the Asia-Pacific region, and future research priorities.